Floral geometric morphometrics unveils a new cauliflorous species of Aristolochia (Aristolochiaceae) from the Guiana Shield - Freitas, Joelcio; González, Favio; Poncy, Odile; Feuillet, Christian; Alves-Araújo, Anderson (Phytotaxa, 2020)
Aristolochia wankeana (Aristolochiaceae), a new species from French Guiana and Guyana, is described and illustrated here. Floral traits, primarily of the shape and size of the perianth limb, examined through a morphometric geometric analysis, are diagnostic to distinguish the new species from its relatives A. cornuta and A. iquitensis. The species belongs to Aristolochia subser. Anthocaulicae, characterized by having extremely short cauliflorous racemes with scale-like, triangular subtending bracts. This is the first study that uses morphometrics for taxonomic purposes in Aristolochia, an approach that becomes promising to solve species complexes in this genus.